2022
DOI: 10.1001/jamanetworkopen.2022.28529
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spending Differences Between Beneficiaries in Medicare Advantage and the Medicare Shared Savings Program

Abstract: IMPORTANCEThe 2 primary efforts of Medicare to advance value-based care are Medicare Advantage (MA) and the fee-for-service-based Medicare Shared Savings Program (MSSP). It is unknown how spending differs between the 2 programs after accounting for differences in patient clinical risk. OBJECTIVE To examine how spending and utilization differ between MA and MSSP beneficiaries after accounting for differences in clinical risk using data from administrative claims and electronic health records. DESIGN, SETTING, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Some leaders reported that these and other trends have introduced difficulties in maintaining participation and engagement in MSSP. The implications of this shift are unclear: a decade after the implementation of ACOs, evidence of their effectiveness remains mixed relative to both traditional fee-for-service payment and the Medicare Advantage program . More research is needed to evaluate outcomes for patients attributed to ACOs vs those in other value-based payment programs, and CMS may also want to devote greater attention to facilitating multipayer ACO models…”
Section: Discussionmentioning
confidence: 99%
“…Some leaders reported that these and other trends have introduced difficulties in maintaining participation and engagement in MSSP. The implications of this shift are unclear: a decade after the implementation of ACOs, evidence of their effectiveness remains mixed relative to both traditional fee-for-service payment and the Medicare Advantage program . More research is needed to evaluate outcomes for patients attributed to ACOs vs those in other value-based payment programs, and CMS may also want to devote greater attention to facilitating multipayer ACO models…”
Section: Discussionmentioning
confidence: 99%
“…Medicare utilizes capitation risk-adjusted payments within the Medicare Advantage program as a pivotal strategy for determining accurate financial arrangements, promoting payment accuracy, and assessing cost control (20). A comparative analysis of spending patterns between Medicare Advantage and the Medicare Shared Savings Program revealed that spending within the latter was 30% higher than in Medicare Advantage (37). This finding assumes added importance when considering projections that the Medicare Advantage program, which has grown from 19% in 2007 to 51% in 2023, is anticipated to encompass over 60% of Medicare beneficiaries by 2030 (38).…”
Section: Discussionmentioning
confidence: 99%
“…While the TM program is still largely paid Fee‐for‐Service and is administered by CMS, the proliferation of alternative payment models (APMs) such as accountable care organizations (ACOs) ACOs and bundled payment programs make it so that the TM program is also not one single exposure. When comparing outcomes between MA and TM, a researcher may find different results when comparing TM beneficiaries attributed to one of these programs, compared to TM beneficiaries not attributed to an APM 19 . For example, several prior studies have found differences in outcomes when comparing MA to TM without ACO attribution to TM with ACO attribution 20 .…”
Section: Methodsmentioning
confidence: 99%
“…When comparing outcomes between MA and TM, a researcher may find different results when comparing TM beneficiaries attributed to one of these programs, compared to TM beneficiaries not attributed to an APM. 19 For example, several prior studies have found differences in outcomes when comparing MA to TM without ACO attribution to TM with ACO attribution. 20 Beyond attribution to APMs in TM, TM beneficiaries do actually have some differences in coverage choices that may also be subject to selection bias.…”
Section: Varying Coverage Choices In Tmmentioning
confidence: 99%